(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
In vitro conservation techniques such as slow growth is now routinely used to compliment conventional conservation approaches. Slow growth procedures provide short to medium term storage options, and offer several advantages such as: free from genetic erosion and convenient for international distribution. The present study is aimed at establishing a slow growth in vitro conservation protocol for Nigerian groundnut varieties. The experiment was conducted with four groundnut varieties: SAMNUT 10, SAMNUT 21, SAMNUT 22 and SAMNUT 23, four conservation media: Murashige and Skoog (MS) media supplemented with different concentrations of sucrose (30, 20,15,10g/L) in combination with different concentrations of mannitol (10,15, 20g/L) and maintained for four different conservation periods: 3, 6, 9 and 12 months. The experiment was arranged as 4 x 4 x4 factorial experiment in a completely randomized design of three replicates. In vitro regenerated shoots of 2cm length were cultured on slow growth media. Results obtained from the study show that maximum survival (33.1%) was observed in SAMNUT 23. While MS medium supplemented with 10g/L sucrose and 20g/L mannitol effectively reduced shoot growth and produced the highest survival (74%) after 3months conservation period. This medium could therefore be used for the medium-term conservation of the groundnut varieties.